Semester Learning Plan Preparation Workshop (RPS) - Rahman, M Arief; Rahmi, Lailatur; Wati, Ade Sukma (Universitas Pejuang Republik Indonesia, 2025)
The Workshop on Semester Learning Plan Development was conducted to support lecturers in understanding how to design structured learning documents aligned with curriculum requirements and classroom learning needs. The activity was initiated based on the need for regular updates of learning plans to ensure that each course has a clear direction and contributes to the expected learning outcomes. The workshop aimed to guide lecturers in reviewing and preparing the core components of the learning plan, including the formulation of course learning outcomes, organization of weekly content, and arrangement of assessment strategies. The method used involved structured training sessions consisting of concept explanations, group discussions, and hands on document drafting. The results indicate an increased understanding among participants in producing more organized and applicable learning plans that are consistent with institutional standards. Participants successfully prepared more comprehensive drafts through collaborative discussions and peer review. Overall, the workshop contributed to improving learning design practices within the higher education environment.